ANALYSIS OF DIFFERENCES IN ABNORMAL RETURN AND TRADING VOLUME ACTIVITY OF COMPANY STOCKS BEFORE AND AFTER THE 2024 PRESIDENTIAL ELECTION - Hermanto, Agus; Saniyah, Eluiz Yansirus (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
This study aims to analyze the differences in average Abnormal Return and Trading Volume Activity (TVA) of stocks listed in the LQ45 index before and after the 2024 Indonesian Presidential Election. The method used is an event study with a 21-day event window, consisting of 10 days before and 10 days after the event. The sample consists of 45 companies listed in the LQ45 index for the February–July 2024 period, selected using purposive sampling. Hypothesis testing was conducted using a paired sample t-test. The results show that there is no significant difference in the average Abnormal Return before and after the presidential election (p = 0.684 > 0.05), while there is a significant difference in Trading Volume Activity (p = 0.029 < 0.05). These findings indicate that although stock prices did not change significantly, trading activity increased after the 2024 election, reflecting investor optimism toward the newly elected government.